Analisis Perilaku Konsumen Cokelat Vicco di Kabupaten Jember - Fauzi, Nurul Fathiyah; Aprillia, Sugesti Dwi (Universitas Galuh, 2025)
One of the main commodities that become the superior of the plantation sector is cocoa. The Covid-19 outbreak has an impact on Vicco's chocolate sales turnover at the Indonesian Coffee and Cocoa Research Center. This study aims to analyze: (1) the profile of respondents and the purchasing decision-making process; (2) the level of consumer satisfaction with Vicco Chocolate.. This research was conducted in Indonesian Coffee and Cocoa Research Center. The selection of this location was done purposively with the consideration that Vicco Chocolate is one of the Counverture chocolate products produced in Jember Regency. The type of research method chosen is descriptive analytical. Determination of sample size was calculated using the Slovin formula with 96 respondents. Data were analyzed using descriptive analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results show that (1) the majority of Vicco Chocolate consumers are female with an age range of 17-25 years, domiciled in Jember, the last education level they have is High School (SMA), works as a student, and has an average income average per month < Rp 1.500.000,-; (2) the consumer satisfaction index as measured by CSI is 77.86%, meaning that the majority of consumers are satisfied with the overall performance of the outlet;